One Step Away From Extinction: A Population Genomic Analysis of A Narrow Endemic, Tropical Plant Species - Teixeira, Thais M.; Nazareno, Alison G. (Frontiers in Plant Science, 2021)
Intraspecific genetic variation plays a fundamental role in maintaining the evolutionary potential of wild populations. Hence, the assessment of genetic diversity patterns becomes essential to guide biodiversity conservation policies, particularly for threatened species. To inform management strategies for conservation of Mimosa catharinensis – a narrow endemic, critically endangered plant species – we identified 1,497 unlinked SNP markers derived from a reduced representation sequencing method (i.e., double digest restriction site associated DNA sequencing, or ddRADseq). This set of molecular markers was employed to assess intrapopulation genetic parameters and the demographic history of one extremely small population of M. catharinensis (N=33) located in the Brazilian Atlantic Forest. Contrary to what is expected for narrow endemic and threatened species with small population sizes, we observed a moderate level of genetic diversity for M. catharinensis [uHE(0%missing data)=0.205, 95%CI (0.160, 0.250); uHE(30%missing data)=0.233, 95%CI (0.174, 0.292)]. Interestingly, M. catharinensis, which is a lianescent shrub with no indication of seed production for at least two decades, presented high levels of outcrossing (t(0%missing data)=0.883, SE ± 0.0483; t(30%missing data)=0.909, SE ± 0.011) and an apparent absence of inbreeding [F(0%missing data)=-0.145, 95%CI (-0.189, -0.101); F(30%missing data)=-0.105, 95%CI (-0.199, -0.011)]. However, the reconstruction of demographic history of M. catharinensis indicated that the population should be suffered a recent bottleneck. Our population genomic study tackles a central issue in evolution and conservation biology and we expect that it will be useful to help safeguard the remaining genetic diversity reported for this unique genetic resource.